2016
DOI: 10.1071/sh15124
|View full text |Cite
|
Sign up to set email alerts
|

How do outcomes compare between women and men living with HIV in Australia? An observational study

Abstract: Background Gender differences vary across geographical settings and are poorly reported in the literature. The aim of this study was to evaluate demographics and clinical characteristics of participants from the Australian HIV Observational Database (AHOD), and to explore any differences between females and males in the rate of new clinical outcomes, as well as initial immunological and virological response to antiretroviral therapy. Methods Time to a new clinical end-point, all-cause mortality and/or AIDS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Conversely, studies from developed countries show differing results, finding no gender differences in clinical, virological and immunological outcomes among HIV infected men and women initiating ART [ 22 , 23 ]. A multi-site cohort study found higher rates of virological rebound in women [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, studies from developed countries show differing results, finding no gender differences in clinical, virological and immunological outcomes among HIV infected men and women initiating ART [ 22 , 23 ]. A multi-site cohort study found higher rates of virological rebound in women [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gender differences in toxicity have been reported for nucleoside analogues , NNRTIs and protease inhibitors (PI) , though clinical trials have not been able to definitively establish sex differences in toxicity risk. Clinical outcomes such as immunological response, new AIDS events, or death, have not been found to significantly differ by sex in either resource‐rich or ‐limited settings .…”
Section: Introductionmentioning
confidence: 95%
“…However, a few studies have suggested no difference between men and women in the response to ART [19–21]. For example, two studies in Australia [22] and Switzerland [23] reported no significant difference between men and women regarding viral load suppression. Given structural and cultural variation across settings, it is possible that the response to ART in men and women is different in less‐developed countries.…”
Section: Introductionmentioning
confidence: 99%